Edcolonising geography?: Disciplinary histories and the end of the british empire in Africa, 1948-1998 - Craggs, Ruth; Neate, Hannah (Hoboken, USA John Wiley & Sons, Inc., 2024)
This book presents an extraordinarily sensitive account of geography$1 (Bs histories in five African countries subjected to British colonial rule. Craggs and Neate draw together political and imaginative processes of decolonisation, through an innovative biographical approach that humanizes and enlivens the story of our academic discipline.s